Operative Versus Nonoperative Treatment of Acute Achilles Tendon Ruptures: A Pilot Economic Decision Analysis. Issue 3 (31st March 2020) - Su, Alvin W.; Bogunovic, Ljiljana; Johnson, Jeffrey; Klein, Sandra; Matava, Matthew J.; McCormick, Jeremy; Smith, Matthew V.; Wright, Rick W.; Brophy, Robert H.
Background: The operative treatment of Achilles tendon ruptures has been associated with lower rerupture rates and better function but also a risk of surgery-related complications compared with nonoperative treatment, which may provide improved outcomes with accelerated rehabilitation protocols. However, economic decision analyses integrating the updated costs of both treatment options are limited in the literature. Purpose: To compare the cost-effectiveness of operative and nonoperative treatment of acute Achilles tendon tears. Study Design: Economic and decision analysis; Level of evidence, 2. Methods: An economic decision model was built to assess the cost-utility ratio (CUR) of open primary repair versus nonoperative treatment for acute Achilles tendon ruptures, based on direct costs from the practices of sports medicine and foot and ankle surgeons at a single tertiary academic center, with published outcome probabilities and patient utility data. Multiway sensitivity analyses were performed to reflect the range of data. Results: Nonoperative treatment was more cost-effective in the average scenario (nonoperative CUR, US520; operative CUR, US1995), but crossover occurred during the sensitivity analysis (nonoperative CUR range, US224-US2079; operative CUR range, US789-US8380). Operative treatment cost an extra average marginal CUR of US1475 compared with nonoperative treatment, assuming uneventful healing in both treatment arms. The sensitivity analysis demonstrated a decreased marginal CUR of operative treatment when the outcome utility was maximized, and rerupture rates were minimized compared with nonoperative treatment. Conclusion: Nonoperative treatment was more cost-effective in average scenarios. Crossover indicated that open primary repair would be favorable for maximized outcome utility, such as that for young athletes or heavy laborers. The treatment decision for acute Achilles tendon ruptures should be individualized. These pilot results provide inferences for further longitudinal analyses incorporating future clinical evidence.